(3MGTjI Ydi OdGFd GdNjQGJ ddLRhdjs - (3jhSa Hf YeQs ((3eMeO GdNWjHs)
(3ChdgG (B:s
(3bGd CHh YHO Gddg Hf eMeO Hf SdjeGf GdLRhdjhHgG Cda cJGHg OdGFd GdNjQGJbhdg HSe Gddg GdQMef GdQMje HJbOje GdHSedI hGaJJGM cJH GdYde HeG Mhi Yed GdCFeI hGdeUfajfs
(3BNQgG (B:s
(3hbhdg hGdMeO ddg QH GdYGdejf hRGO aj HYV LO gPG hgh MSHfG hfYe Gdhcjd hcJH GdTjN QVj Gddg Yfg gfG aj WQI NJe GdcJGH ef GdfSNI GdSgjdjIs
(3aj Chdg JQLeI dCHj YHO Gddg Hf SdjeGf GdLRhdj GdSedGfj eDda eJf OdGFd GdNjQGJs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs